Yes, they are exacty the same answer- though with different "C".
If you multiply both sides of C= 2sqrt(y)+ ix by -i you get -Ci= x- 2i sqrt(y).
dy/dx = -i sq root (y)
If the variables are separated in such a way that sq.root of y goes on the left side and "i" remains on the right then the answer is C = 2 sq. root(y) +ix.
But if the variables are separated in such a way that i sq.root (y) is taken to the left leaving -1 on the right then the answer turns out to be C = x - i*2* sq. root(y).
Are both of these correct ?
Please help .